Membranoproliferative Glomerulonephritis Preceding Non-Hodgkin Lymphoma Recurrence: A Case Report - Meltem Sezis Demirci; Cenk Gokalp; Cenk Demirci; Emrah Gunay; Ayhan Donmez; Sait Sen; Mehmet Ozkahya (Archives of Renal Diseases and Management - Peertechz Publications, 2016)
Introduction: Membranoproliferative glomerulonephritis has been reported to occur in association with non-Hodgkin's lymphoma but there is few information about glomerulonephritis response to the treatment of non-Hodgkin's lymphoma. Case Presentation: A 67 years-old caucasian female admitted to outpatient clinic with peripheral edema complaint. She had mild proteinuria and microhematuria on admission and tuberculosis, non-Hodgkin lymphoma (cured), diabetes mellitus and hypertension history. Her renal biopsy resulted as  membranoproliferative  glomerulonephritis  and  after  investigations  she  got  recurrent  non-Hodgkinlymphoma  diagnosis.  After  successful  treatment  of  her  lymphoma  her  nephrotic  syndrome  clinicregressed. Conclusion: Membranoproliferative  glomerulonephritis  has  been  known  to  be  associated with  non-Hodgkin's  lymphoma.  There  is  limited  information  available  concerning  the  effects  of treatment of non-Hodgkin's lymphoma on the progression of non-Hodgkin's lymphoma associated membranoproliferative  glomerulonephritis.  We  report  a  rare  case  of  non-Hodgkin's  lymphoma associated  membranoproliferative  glomerulonephritis,  that  continued  to  be  in  remission  after chemotherapy treatment of lymphoma.